Measuring the evolution of competition and the impact of the financial reform in the Mexican banking sector, 2008-2019 - Enrique Bátiz-Zuk; José Luis Lara Sánchez (Banco de México, 2021)
This paper analyzes the monthly evolution of bank competition in Mexico from 2008 to 2019 using different measures. Subsequently, we analyze whether the 2014 financial reform had an effect on some of our competition measures. We use ordinary and quantile regression techniques and Markov switching models to identify changes in regimes. We find partial empirical evidence supporting the idea that the reform had a positive average effect and increased banks competition intensity during a few years. However, we also document heterogeneity as some large banks benefited from an increase in their market power. We perform several robustness tests and report that our measures lead to values that are congruent and similar to those available in the literature. The main policy lesson of our research is that regulators could benefit from the monitoring of competition evolution using a finer time frequency.
Keywords: D40; G21; G28; L10; L11; L50; 330; competition measures; regulatory impact; financial reforms; banks; bank mergers